All‐Solution‐Processed Ultrahigh Broadband and Wide‐Angle Perfect Absorber Based on Mxene–Gold Nanoparticles. Issue 21 (16th August 2020) - Ali, Wajid; Mideksa, Megersa F.; Hou, Ke; Li, Hongdong; Wang, Xiaoli; Tang, Zhiyong
Abstract: Broadband perfect absorbers are of great importance for various applications such as stealth technologies, thermal photovoltaic cells, optical communication, photodetection, and photovoltaic devices. However, they are often made by lithographic techniques with high cost and complexity, which hinders their practical applications. The design of broadband and ultrahigh absorber at low cost and ease in fabrication is still a big challenge in the field of optics. Here, an all‐solution‐processed plasmonic perfect absorber is proposed and demonstrated by incorporating Mxene Ti3 C2 T x (T x = F, O or OH) and gold nanoparticles (NPs) in metal–insulator–metal configuration. The absorption of the designed plasmonic absorber can reach up to 99% with polarization‐ and angle‐independence in a broad range of wavelengths from ultraviolet to near‐infrared region. This ultrahigh and broadband absorbance is attributed to the synergy of plasmon resonance, magnetic resonance, and cavity effect between gold NPs layer and Mxene film, which is further corroborated by simulations of the finite element method for both random and patterned orientation of the gold nanoparticles. The excellent optical property together with the easy fabrication method paves the way for preparing photon‐absorbing nanostructures in photocatalysis and solar photovoltaics. Abstract : An all‐solution‐processed plasmonic perfect absorber is proposed and demonstrated by incorporating Mxene and gold nanoparticles in the metal–insulator–metal configuration. The absorption of the absorber can reach to 99% with polarization‐ and angle‐independence from ultraviolet to near‐infrared. The excellent optical property together with the easy fabrication method paves the way for preparing photon‐absorbing nanostructures in photocatalysis and solar photovoltaics.